2008
DOI: 10.1093/rpd/ncn241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CONRAD computational problems expressing only stochastic uncertainties: neutrons and protons

Abstract: Within the scope of CONRAD (A Coordinated Action for Radiation Dosimetry) Work Package 4 on Computational Dosimetry jointly collaborated with the other research actions on internal dosimetry, complex mixed radiation fields at workplaces and medical staff dosimetry. Besides these collaborative actions, WP4 promoted an international comparison on eight problems with their associated experimental data. A first set of three problems, the results of which are herewith summarised, dealt only with the expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A tin (Sn) layer was placed above the steel to filter additional X-rays that were formed during γ-filtering in the steel. The moderated ~0.1 eV neutrons [ 19 ] travelled through an air layer before finally reaching the Gd-coated Si wafer. The total source to-detector distance was 11.7 cm, close to the 10.6 cm reported previously [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A tin (Sn) layer was placed above the steel to filter additional X-rays that were formed during γ-filtering in the steel. The moderated ~0.1 eV neutrons [ 19 ] travelled through an air layer before finally reaching the Gd-coated Si wafer. The total source to-detector distance was 11.7 cm, close to the 10.6 cm reported previously [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whilst MC methods are well benchmarked, their use is still subject to significant user influence. Intercomparisons have been used to demonstrate that, even for relatively simple problems, users can get results that are in error by several orders of magnitude (Gualdrini et al., 2008). These problems can result from minor mathematical errors, but they can also be caused by erroneous specification of the problem or the use of inappropriate physics.…”
Section: Eurados Scientific Work Programmementioning
confidence: 99%
“…Various transport codes are suited to calculate the response matrix of a BSS. A recent computational exercise (38) organised in the framework of the CONRAD project demonstrated that the MCNP family is used in the majority of the cases. FLUKA (39,40) and GEANT 4 (41) have also been used, obtaining comparable results.…”
Section: The Response Of the Bssmentioning
confidence: 99%